Diversity analysis of Erysiphe pisi populations causing pea powdery mildew in Himachal Pradesh - SACHIN UPMANYU, JAYA CHAUDHARY; P.N. SHARMA, D.K. BANYAL*, AMAR SINGH (Indian Phytopathology, 2014)
Powdery mildew of pea caused by Erysiphe pisi DC ex. Saint-Amans is of common recurrence and destructive disease in wet and dry temperate regions of Himachal Pradesh where pea is an important off-season crop. Knowledge of virulence pattern of the pathogen is of paramount importance to explore host resistance and there is no well documented proof of pathogenic variation in powdery mildew pathogen except few reports, probably due to lack of availability of defined differential set. In the present study, a differential set of nine pea genotypes was developed from a panel of 317 pea lines comprising of exotic and indigenous collections with differential resistance to powdery mildew isolates. Virulence analysis of 36 isolates representing diverse pea growing areas of Himachal Pradesh determined on a differential set of pea genotypes viz., JI-2302 (er1), EC-334160, NIC-11181, EC-292164, EC-329561, JI-1559 (er1), JI-2480 (er2), PB29B and Lincoln (check) showed the presence of 19 pathotypes of E. pisi in the target area of study. Three pathotypes PMP 12, 14 and 18 were found highly virulent infecting five differentials whereas PMP 7 was least virulent showing resistant reaction on all the differentials.